2014
DOI: 10.1136/bmjopen-2013-004138
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric measurements of general and central obesity and the prediction of cardiovascular disease risk in women: a cross-sectional study

Abstract: ObjectivesIt is important to ascertain which anthropometric measurements of obesity, general or central, are better predictors of cardiovascular disease (CVD) risk in women. 10-year CVD risk was calculated from the Framingham risk score model, SCORE risk chart for high-risk regions, general CVD and simplified general CVD risk score models. Increase in CVD risk associated with 1 SD increment in each anthropometric measurement above the mean was calculated, and the diagnostic utility of obesity measures in ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 78 publications
5
97
1
5
Order By: Relevance
“…Obesity is a major risk factor for hypertension, as well as cardiovascular disease, diabetes, cancers, and musculoskeletal disorders (WHO, 2008;Nguyen and Lau, 2012). Measures of central obesity predict metabolic syndrome, type 2 diabetes, cardiovascular disease, and all-cause mortality better than body mass index (BMI) (Visscher et al, 2001;Goh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a major risk factor for hypertension, as well as cardiovascular disease, diabetes, cancers, and musculoskeletal disorders (WHO, 2008;Nguyen and Lau, 2012). Measures of central obesity predict metabolic syndrome, type 2 diabetes, cardiovascular disease, and all-cause mortality better than body mass index (BMI) (Visscher et al, 2001;Goh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…WHR is a strong predictor of cardiovascular risk (34). We found that subjects homozygous for the d3-GHR had larger WHR in two independent cohorts of adult Swedes.…”
Section: European Journal Of Endocrinologymentioning
confidence: 79%
“…Под эгидой Национального фонда сердца Австра-лии было проведено популяционное исследование по изучению распространенности ФР ССЗ среди жен-щин [18]. В исследование было включено 4487 жен-щин в возрасте 20-69 лет без заболеваний сердца, СД 2 типа и инсультов в анамнезе.…”
Section: ожирение как фактор риска хронических неинфекционных заболевunclassified